Growth, Sporulation, Conidial Germination and Lethal Temperature of Paraphoma radicina, A Fungal Pathogen of Alfalfa (Medicago sativa) Root Rot - Shi Cao; Yan-Zhong Li (Agriculture, 2022)
In 2020, alfalfa root rot, a disease caused by Paraphoma radicina, was identified in Inner Mongolia, China, where it seriously affected alfalfa crop yields. Conditions for in vitro growth, sporulation and conidial germination of P. radicina are poorly understood, limiting further studies. In this contribution, we evaluated the suitability of different media, carbon and nitrogen sources, as well as temperature and pH for P. radicina in vitro growth and germination. In addition, the temperature sensitivity of these cultures was assessed. Paraphoma radicina growth and sporulation were most vigorous on the ARDA medium, reaching the maximum growth and sporulation rates after 4 weeks of incubation. All carbon and nitrogen sources supported growth, but none induced sporulation. The best carbon and nitrogen sources for growth were mannitol and peptone, respectively. Conidial germination was observed in the 4 to 35 °C temperature range, with an optimum temperature of 25 °C. The germination rate was highest at pH 7, and more than 50% of conidia germinated after 38 h of incubation at 25 °C. On the other hand, temperatures above 55 °C (10 min) and 41 °C (10 min) proved lethal for the mycelial and conidial forms of the pathogen, respectively. These results can provide clues to the environmental conditions amenable for P. radicina infection of alfalfa crops and, on the whole, a better understanding of pathogenicity.